Genetic Control of Beta-carotene, Iron and Zinc Content in Sweetpotato - Baafi, E.; Ofori, K.; Carey, E.E.; Gracen, V.E.; Blay, E.T.; Manu-Aduening, J. (Canadian Center of Science and Education, 2016)
Micronutrients deficiency is a major contributor to poor health in developing countries. It can be alleviated by biofortification or enrichment of staple crops with micronutrients. Sweetpotato is a major staple crop in numerous tropical countries and is naturally biofortified. In spite of extensive promotion of orange-fleshed sweetpotato varieties (OFSPs), they are poorly utilized as staple food in most parts of West Africa because of their low dry matter and high sugar content. Beta-carotene is positively correlated with iron and zinc content in sweetpotato. Development of sweetpotato cultivars with end-user preferred traits and higher content of beta-carotene, iron and zinc will alleviate their deficiencies. Knowledge on the genetic control of these traits is critical for their improvement in sweetpotato. This study used diallel mating design to estimate general combining ability (GCA) and specific combining ability (SCA) of storage root beta-carotene, iron and zinc content to determine the genetic control of these traits for sweetpotato breeding. A general model for estimating genetic effect, Gardner and Eberhart analysis II (GEAN II), was used for data analysis. Genetic variability for the traits indicated that they were mostly controlled by additive gene effect. Significant heterosis was found indicating that levels of these micronutrients can be improved in sweetpotato through breeding.